Pleural empyema - Crisanto Abad Celuria; José Antonio Santana Santana; Abel Santana González-Chávez; Narciso Hernández Rodríguez; Leonardo Rodríguez Tapanes; Daniel Gutiérrez Hidalgo-Gato (Medisur)
Empyema is accumulation of puss in the cavity pleural, that can occupy part or all of it. The inflammatory fluid and the fibrin inside the pleural space is the result of an infection inside the pleural cavity that changes of watery liquid to suppurative collection inside the same one. Majority of parapneumonics discharges resolve without complications and with little clinical meaning, but some of they becomes empiema. We presented the Good Clinical Practices Guideline for Pleural empyema, approved by consensus in the 4th National Good Clinical Practices Workshop in Pediatric Surgery (Las Tunas, Cuba, March, 2005).